Sosialisasi Mengenai Teknologi Digital Yang Berpengaruh Terhadap Perilaku Peserta Didik - Rizki Fadilla, Dina; Sari, Meylia; Bahar, Yolanda; Salim, Agus; Purnama, Rina (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2024)
Students' lives will always be influenced by technology. Not only at school, students at home also collaborate with technology. In fact, modern technology makes everything simpler. On the contrary, students tend to be lethargic and want everything immediately because of technology. This is because students often have easy access to everything quickly / instantly. So, if they experience an obstacle, students want to solve the obstacle instantly and without thinking twice. The purpose of implementing this PKM is to provide knowledge through socialization to students about digital technology that affects the behavior of students. This community service activity is carried out using discussion methods, Q&A and programmed lectures, according to the summary that the PKM team has prepared. The results obtained from this activity were when the PKM team asked questions to the students, some of the students answered that with the current digital technology they can very easily find out about developments in the outside world and easily gain insight into the learning they are undergoing, some others admitted that by often playing gadgets (cellphones) they become lazy to read books or look for learning materials directly from books, they prefer to look for answers or something from Google Internet only